Penguasaan Konsep dan Kreativitas Siswa Kelas IV pada Materi Gerak Melalui Pembelajaran RADEC Menggunakan Zoom Meeting - Oktaviani, Ike; Sujana, Atep; Djuanda, Dadan (Jurnal Pena Ilmiah, 2021)
This research is based on the researcher's interest in Radec learning which is used for online learning and seeing students' mastery and creativity. In online Radec learning, students feel happy because the teacher makes learning fun and not boring. Students feel happy because they can discuss with their group friends and also students can try various kinds of motion of objects that occur in everyday life. The purpose of this study was to determine the implementation of Radec learning using zoom meetings, to see students' mastery of concepts and creativity after learning through Radec learning using zoom meetings. This research method is descriptive qualitative. The subjects of this study were all fourth grade students of SDS Sariputra, Lemahwungkuk sub-district, Cirebon City. The instruments used are observation, interviews, and evaluation tests. Observations and interviews are used to see the implementation of learning, evaluation tests are used to see students' mastery and creativity. The results of this study showed that Radec's learning was carried out well with the delivery of good teachers, and it was seen that students mastered the concept and could explain the concept again using their own language, and students creativity was seen from the varied student answers.